Analisa Kelayakan Ekonomi Pembangunan Jalur Kereta Api Minang Kabau International Airport (MIA) Sumatera Barat - Rizaldi, Nulvi; Taufik, Hendra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The province of West Sumatera has the presticigious international airport is known as Minangkabau International Airport (MIA). It provide positive impacts for additional traffic for aircraf. Due to that, the MIA needs a special airport transportation to encourage this faciltiy, such as Railbus. Due toThe railway construction consumes a lot of cost, it necessary to anaiyse its benefits and disadvantages. The purpose of this research is to carry out the economic feasibility of railway construction the Minangkabau International Airport (MIA) in West Sumatera. This research focus on the cost of railway construction, cost revenues from the carriage of passengers and economic feasibility analysis by using method of Net Present Value (NPV), Benefit Cost Ratio (BCR), Internal Rate of Return (IRR) and Break Even Point (BEP), sensitivity analysis and based on three travelling scenarios . The result of this study may also useful for recommendation to the stakeholders. As a result, the cost Railbus investment is Rp. 133.731.000.000,-, by using an interest rate of 10,5%, is obtained for the first scenario NPV = – Rp. 175.175.021.608, BCR = 0,52, IRR = 8,11% , the second scenario NPV = – Rp. 54.783.535.897, BCR = 0,83, IRR = 3,42%, and the third scenario NPV = Rp. 86.922.386.390, BCR = 1,24, IRR = 9,23%. The results of the feasibility study analysis shown that investment for the first and second scenarios, all the parameters indicated the investment is inappropriate to be constructed. The third scenario indicated the investment is feasible to be constructed. Key Words : Railbus, MIA, Feasibility Study, Sensitivity Analysis